2017
DOI: 10.3892/mmr.2017.6684
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of asiatic acid in a spontaneous type 2 diabetic mouse model

Abstract: Asiatic acid (AA) has been demonstrated to exhibit anti-diabetic activity. However, the mechanisms and underlying signaling pathways remain to be elucidated. The present study was performed to confirm the protective effect of AA and demonstrate its ability to regulate the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT)/glycogen synthase kinase-3β (GSK-3β) signaling pathway in db/db mice. Db/db mice fed on a high-fat diet were used to model diabetes mellitus. Modeled mice were divided randomly into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…Mechanistically, it promoted cell survival machinery by promoting activation of Akt kinase and Bcl-xL in the pancreatic islets. The antidiabetic activity of AA was shown mediating PI3K/AKT/GSK-3β signaling mechanism in high-fat diet fed db/db mice (Sun et al, 2017 ). AA attenuated rise in expression of PI3K, AKT, insulin receptors, and insulin receptor substrate-1 and downregulated GSK-3β and glucose-6-phosphatase.…”
Section: Asiatic Acid In Diabetesmentioning
confidence: 99%
“…Mechanistically, it promoted cell survival machinery by promoting activation of Akt kinase and Bcl-xL in the pancreatic islets. The antidiabetic activity of AA was shown mediating PI3K/AKT/GSK-3β signaling mechanism in high-fat diet fed db/db mice (Sun et al, 2017 ). AA attenuated rise in expression of PI3K, AKT, insulin receptors, and insulin receptor substrate-1 and downregulated GSK-3β and glucose-6-phosphatase.…”
Section: Asiatic Acid In Diabetesmentioning
confidence: 99%
“… 25 Asiatic acid is another pentacyclic triterpene showing hypoglycemic activity in different diabetic animal models. 10 , 26 , 27 We have observed that asiatic acid effectively prevents cardiomyocyte apoptosis after oxygen-glucose deprivation/ reperfusion injury. 11 Taken together, we hypothesized that asiatic acid may protect against ischemia/reperfusion injury by modulation of glycometabolism in cardiomyocyte.…”
Section: Discussionmentioning
confidence: 96%
“…However, asiatic acid, as an active compound in C. asiatica, has anti-inflammatory activity by downregulating the pro-inflammatory cytokines IL-6, IL-1β, and TNF-α in human corneal epithelial cells and the liver tissue of diabetic-induced mice (12,13). In addition, asiatic acid exerts anti-hyperglycemia effect in high fat diet (HFD)-induced diabetes mice through the PI3K/Akt/GSKβ signaling pathway (21). Another previous study showed that asiatic acid at a dose of 20 mg/kg body decreased blood-glucose level in diabeticinduced rat using streptozotocin (STZ) followed by improved glucose uptake into skeletal muscle tissues via the IRS-1/PI3K-Akt signaling pathway (22).…”
Section: Discussionmentioning
confidence: 99%